2000
DOI: 10.1093/emboj/19.3.359
|View full text |Cite
|
Sign up to set email alerts
|

FHL2, a novel tissue-specific coactivator of the androgen receptor

Abstract: The control of target gene expression by nuclear receptors requires the recruitment of multiple cofactors. However, the exact mechanisms by which nuclear receptor-cofactor interactions result in tissue-specific gene regulation are unclear. Here we characterize a novel tissue-specific coactivator for the androgen receptor (AR), which is identical to a previously reported protein FHL2/DRAL with unknown function. In the adult, FHL2 is expressed in the myocardium of the heart and in the epithelial cells of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
283
3
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(307 citation statements)
references
References 60 publications
20
283
3
1
Order By: Relevance
“…Therefore FHL3 was believed to bind specifically MZF-1 among the FHL family members, which would lead to the results in Figure 5(D) where FHL3 but not FHL1 and FHL2 inhibited the β-chain promoter activity. Although LIM proteins regulate transcription in the nucleus [28][29][30], the LIM zinc finger does not interact with DNA but with proteins [31,32]. This coincides with our results that FHL3 itself did not modulate the FcεRI β-chain gene transcription in the absence of MZF-1 ( Figure 5F).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore FHL3 was believed to bind specifically MZF-1 among the FHL family members, which would lead to the results in Figure 5(D) where FHL3 but not FHL1 and FHL2 inhibited the β-chain promoter activity. Although LIM proteins regulate transcription in the nucleus [28][29][30], the LIM zinc finger does not interact with DNA but with proteins [31,32]. This coincides with our results that FHL3 itself did not modulate the FcεRI β-chain gene transcription in the absence of MZF-1 ( Figure 5F).…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Figure 1B, the chimeric GAL4-DBD-FHL2 protein only weakly activated the GAL4-dependent reporter gene, by approximately three-to four-fold in these cells, which is consistent with previous reports (28,29). The luciferase activity was significantly enhanced by cotransfection of GAL4-DBD-FHL2 with the VP16-Id2-DBM or VP16-Id2-DBM-dHLH vector in a dose-dependent manner ( Figure 1B).…”
Section: Two-hybrid Screening Identifies Fhl2 As An Id2-interacting Fsupporting
confidence: 91%
“…Functional significance of cytoplasmic expression is not clear but, in this context, it should be noted that similar observations were made for the co-activators FHL2 and RAC3. 13,53 Because of its association with a number of molecules that control proliferation and apoptosis, CBP is a good candidate to be involved in ligand-independent activation of the AR, as recently demonstrated in the case of interleukin-6. 54 Taken together, findings of our study and those reported by others indicate that the transcriptional co-activator CBP might be considered a potential therapy target in prostate cancer.…”
Section: Discussionmentioning
confidence: 98%